Hypertension prevalence, associated factors, treatment and control in rural Cameroon: a cross-sectional study - Valirie Ndip Agbor; Larissa Pone Simo; Dora Mbanya; Jean Jacques N Noubiap; Orlin Pagnol Nana; Pride Swiri-Muya Nkosu; Arnold Forlemu Asaah Anouboweh; Jude Nfor Ndi; Jacques Nguend Mbock; Noel Fils Bakari; Harold Giovani Guifo Tambou (BMJ Open)
Introduction Sub-Saharan Africa is experiencing a surge in the burden of hypertension, and rural communities are increasingly affected by the epidemic.Objectives We aimed to determine the prevalence of and factors associated with hypertension in rural communities of the Baham Health District (BHD), Cameroon. In addition, we sought to assess awareness, treatment and control rates of hypertension among community members.Design A community-based cross-sectional study.Setting Participants from five health areas in the BHD were recruited from August to October 2018.Participants Consenting participants aged 18 years and above were included.Results We included 526 participants in this study. The median age of the participants was 53.0 (IQR=35–65) years and 67.1% were female. The crude prevalence of hypertension was 40.9% (95% CI=36.7–45.1) with no gender disparity. The age-standardised prevalence of hypertension was 23.9% (95% CI=20.3–27.5). Five-year increase in age (adjusted OR (AOR)=1.34; 95% CI=1.23–1.44), family history of hypertension (AOR=2.22; 95% CI=1.37–3.60) and obesity (AOR=2.57; 95% CI=1.40–4.69) were associated with higher odds of hypertension after controlling for confounding. The rates of awareness, treatment and control of hypertension were 37.2% (95% CI=31.0–43.9), 20.9% (95% CI=16.0–26.9) and 22.2% (95% CI=12.2– 37.0), respectively.Conclusion The high prevalence of hypertension in these rural communities is associated with contrastingly low awareness, treatment and control rates. Age, family history of hypertension and obesity are the major drivers of hypertension in this community. Veracious policies are needed to improve awareness, prevention, diagnosis, treatment and control of hypertension in these rural communities.